ANÁLISE NUTRICIONAL DE CARDÁPIOS OFERTADOS EM UAN DA REGIÃO NOROESTE DO RIO GRANDE DO SUL - Neuberger, Suelen; Boff, Charles J. T.; Shimanoski, Vanderléa M.; Bellé, Tânia R. L.; Rodrigues, Taize A. (Salão do Conhecimento, 2013)
Resumo